Comparative analysis between classical and third-order sliding mode controllers for maximum power extraction in wind turbine system - Bourouina, A.; Taleb, R.; Bachir, G.; Boudjema, Z.; Bessaad, T.; Saidi, H. (Національний технічний університет "Харківський політехнічний інститут", 2025)
Maximizing power extraction in wind energy conversion systems is crucial for efficiency but remains a challenge due to rapid wind speed variations and the high inertia of the generator. Conventional controllers, such as the PI controller, struggle to maintain optimal performance under such dynamic conditions, leading to suboptimal power capture and increased system oscillations. The goal of this study is to enhance the efficiency of wind turbine systems by applying linear and nonlinear controllers in a maximum power point tracking (MPPT) strategy. This approach focuses on improving generator speed regulation and power conversion performance. Methods. A comparative analysis is conducted using three different control strategies: third-order sliding mode control (TO-SMC), classical slidin mode control (SMC) and PI control. These controllers are implemented in the generator speed loop of a wind turbine system, and their performance is evaluated through MATLAB/Simulink simulations. The assessment focuses on key performance metrics such as tracking accuracy, total harmonic distortion (THD), response time, and system stability. Results. The simulation results confirm that all controllers achieve MPPT, but with varying levels of effectiveness. The TO-SMC outperforms both SMC and PI controllers, offering higher efficiency, reduced chattering, better disturbance rejection, and lower THD (reduced from 73 % in SMC to 68.09 %). Additionally, TO-SMC significantly improves dynamic response, reducing overshoot and enhancing system stability. Originality. This study introduces a TO-SMC for MPPT in wind turbine systems, demonstrating its superiority over conventional control techniques. The findings highlight its ability to maintain optimal power extraction even under rapid wind variations, making it a promising solution for advanced wind energy systems. Practical value. By improving power quality, reducing system oscillations, and enhancing overall wind turbine efficiency, the proposed TOSMC contributes to the reliable integration of wind energy into power grids. These advancements can benefit renewable energy operators, power system engineers, and researchers seeking efficient and robust MPPT solutions for wind turbines.

Максимізація відбору потужності в системах перетворення енергії вітру має вагоме значення для ефективності, але залишається проблемою через швидкі зміни швидкості вітру та високу інерцію генератора. Звичайні контролери, такі як ПІ-контролер, важко підтримують оптимальну продуктивність в таких динамічних умовах, що призводить до неоптимального відбору потужності і збільшення коливань системи. Метою статті є підвищення ефективності систем вітряних турбін шляхом застосування лінійних та нелінійних контролерів у стратегії відстеження точки максимальної потужності (MPPT). Цей підхід фокусується на покращенні регулювання швидкості генератора та продуктивності перетворення енергії. Методи. Порівняльний аналіз проводиться з використанням трьох різних стратегій управління: керування ковзним режимом третього порядку (TO-SMC), класичне керування ковзним режимом (SMC) та ПІ-керування. Ці контролери реалізовані в контурі швидкості генератора системи вітряних турбін, а їх продуктивність оцінюється за допомогою моделювання MATLAB/Simulink. Оцінка фокусується на ключових показниках продуктивності, таких як точність відстеження, повне гармонічне спотворення (THD), час відгуку та стабільність системи. Результати моделювання підтверджують, що ці контролери досягають MPPT, але з різним рівнем ефективності. TOSMC перевершує як SMC, так і ПІ-регулятори, пропонуючи більш високу ефективність, знижене коливань, краще зменшує перешкоди та має менше THD (знижений з 73 % у SMC до 68,09 %). Крім того, TO-SMC значно покращує динамічний відгук, зменшуючи перерегулювання та підвищуючи стабільність системи. Оригінальність. Це дослідження представляє TO-SMC MPPT в системах вітряних турбін, демонструючи його перевагу над традиційними методами управління. Результати підкреслюють його здатність підтримувати оптимальний відбір потужності навіть за швидких змін вітру, що робить його перспективним рішенням для сучасних вітроенергетичних систем. Практична цінність. За рахунок покращення якості електроенергії, зниження коливань системи та підвищення загальної ефективності вітрових турбін пропонований TO-SMC сприяє надійній інтеграції енергії вітру в електромережі. Ці досягнення можуть принести користь операторам відновлюваних джерел енергії, інженерам енергосистем та дослідникам, які шукають ефективні та надійні рішення MPPTдля вітрових турбін.
Keywords: wind turbine; maximum power point tracking; third-order sliding mode control; variable speed wind turbines; вітряна турбіна; відстеження точки максимальної потужності; керування ковзним режимом третього порядку; вітряні турбіни зі змінною швидкістю